2023
DOI: 10.1101/2023.03.08.23286720
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potentiation of Cortico-Spinal Output via Targeted Electrical Stimulation of the Motor Thalamus

Abstract: Cerebral white matter tract lesions prevent cortico-spinal descending inputs from effectively activating spinal motoneurons, leading to untreatable muscle paralysis. However, in most cases the damage to cortico-spinal axons is incomplete and the spared connections could be potentiated by neurotechnologies to restore motor function. Here we hypothesized that, by engaging direct excitatory connections to cortico-spinal motoneurons, deep brain stimulation (DBS) of the motor thalamus could facilitate activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 106 publications
0
13
0
Order By: Relevance
“…15 Interestingly, these results were replicated in a human patient with chronic TBI with rightsided hemiparesis. 15 DBS of the motor thalamus led to significantly increased grip strength that persisted even after the DBS was turned off. 15 There is also evidence to suggest that DBS improves cognitive and psychological dysfunction in TBI patients.…”
Section: Traumatic Brain Injurymentioning
confidence: 83%
See 1 more Smart Citation
“…15 Interestingly, these results were replicated in a human patient with chronic TBI with rightsided hemiparesis. 15 DBS of the motor thalamus led to significantly increased grip strength that persisted even after the DBS was turned off. 15 There is also evidence to suggest that DBS improves cognitive and psychological dysfunction in TBI patients.…”
Section: Traumatic Brain Injurymentioning
confidence: 83%
“…15 DBS of the motor thalamus led to significantly increased grip strength that persisted even after the DBS was turned off. 15 There is also evidence to suggest that DBS improves cognitive and psychological dysfunction in TBI patients. Kuhn et al 16 report that DBS targeting the hypothalamus eliminated post-TBI self-mutilation behavior in a 22-year-old woman.…”
Section: Traumatic Brain Injurymentioning
confidence: 97%
“…It has been demonstrated that DBS of the motor thalamus leads to increased voluntary movement of the paretic limb in nonhuman primates. 15 Interestingly, these results were replicated in a human patient with chronic TBI with rightsided hemiparesis. 15 DBS of the motor thalamus led to significantly increased grip strength that persisted even after the DBS was turned off.…”
Section: Traumatic Brain Injurymentioning
confidence: 83%
“…We designed an experimental setup in anesthetized macaque monkeys (n=2; Mk-JC, Mk-Ka), who share with humans monosynaptic corticospinal innervations of spinal motoneurons 31,32 . Briefly, to replicate our simulations in a controlled fashion, we applied SCS at C6-C8 cervical spinal segments, while manipulating supraspinal input by means of deep-brain stimulation of the internal capsule 33 , which is a deep-brain structure hosting corticospinal fibers. In parallel, we measured motoneuron output directly, via intraspinal neural recordings, and indirectly, via evoked intramuscular electromyographic (EMG) in the hand muscles ( Fig.…”
Section: Resultsmentioning
confidence: 99%